Effect of polycarboxylate ether (PCE) addition to physical and mechanical characteristics of high performance concrete - Ali, Maisarah; Ahmad, Muhamad Zharif; Saad , Siti Asmahani (Trans Tech Publications, Switzerland, 2015)
Abstract. Conventional concrete does not have durability and higher strength as produced by high performance concrete (HPC). It is known that the HPC possess the following three properties which are high workability, high strength, and durability. The introduction of polycarboxylate ether (PCE) superplasticizer was proved to enhance the workability of concrete even though at a lower water to cement ratio. The study was conducted to find the optimum dosage of PCE and to compare its compressive strength, physical characteristics and morphology of the HPC. The result of the test shows that the high performance concrete (HPC) with addition of 0.5% polycarboxylate ether (PCE) superplasticizer of the cement mass have the highest compressive strength and excellent physical properties.